UZBEKISTAN RAILWAYS JOINT STOCK COMPANY THE ROLE OF FINANCIAL ANALYSIS IN OPTIMIZING THE EFFICIENCY OF LOGISTICS CORPORATE STRUCTURES - Makhmudov Samariddin Bakhriddinovich; Mamarayimova Rushana Rashidovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Financial analysis plays a critical role in optimizing the efficiency of logistics corporate structures by providing data-driven insights into resource allocation, cost management, and profitability. This paper explores the integration of financial analysis into logistics operations, highlighting how financial performance metrics such as cash flow, profitability, and return on investment drive strategic decisions that enhance operational efficiency. By evaluating logistics costs, including transportation, warehousing, and inventory management, financial analysis enables companies to streamline processes and reduce inefficiencies. Moreover, the study examines the use of financial tools like ratio analysis, budget forecasting, and break-even analysis to assess the financial health of logistics firms. The findings emphasize the importance of financial analysis in identifying areas for investment in digital technologies, optimizing supply chain operations, and ensuring sustainable financial growth. This approach ultimately supports the overall goal of improving the economic viability and competitive edge of logistics corporate structures